Development of a novel moulding technique to produce a unique gummy confectionery product : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Mechatronics, Massey University, Albany, New Zealand - Smith, David J. (Massey University, 2020)
ZURU Toys, one of the fastest growing toy companies in the world, identified an opportunity to capitalise on a unique opportunity within the growing confectionery industry by creating a product to merge a surprise toy egg with a unique gummy confectionery experience. The concept was to have a plastic surprise toy capsule shaped as an egg, which was to be encapsulated by gummy laid out in a spiral of eight distinctive colour strips. The gummy strips were to be peeled off the surface of the egg capsule and consumed to reveal the capsule housing the surprise toy. ZURU partnered with Massey University’s Engineering and Food Technology departments to explore the product opportunity further. The project was given to the Engineering Department, as there was no clear method for creating the product with existing manufacturing techniques. The client commissioned the project with virtually no constraints attached with the intention that the department would have complete freedom to explore all possible methods of manufacturing the product concept on a mass scale. The purpose of this thesis is to explore appropriate manufacturing techniques which can be used to mass manufacture the desired gummy confectionery product. To address the complexity of the client’s desired confectionery product, a feasibility analysis of injection moulding techniques is investigated. To gather the necessary understandings for developing a solution to this concept, the two industries relevant to this study, Gummy Confectionery Production and Mass Manufacturing of Polymers, are explored in a literature review. Early stage material testing was done to understand how the material behaves. This process included fabricating the first aluminium mould concept to explore the behaviours of gummy moulding in aluminium. This testing led to the development of the first mould concept. Following several mould iterations and subsequent testing, a clear understanding of how the egg could be produced at a mass scale was documented. The final mould concept was a two-part egg-shaped aluminium mould with seven spiral ribs sectioning off the eight cavities, with the toy capsule acting as a centre core. At the correct volumes, different coloured gummy could be injected into each cavity to encase the egg capsule with a spiral effect of eight distinctive strips of gummy. By following the ideal test conditions of injecting gummy at 60°C and cooling the mould for four minutes in water at 3°C it was possible to manufacture a gummy egg of the described characteristics at the scale described by the client. The mould designs and requirements for manufacturing the product on a mass scale was subsequently delivered to the client which has since filed for patent protection on the method in select countries and implemented the solution on an automation line in a food safe factory in China in preparation for launch.
The following Figures were removed for copyright reasons, but may be accessed via their source listed in the References: Figs 12 & 18 (=Xie et al., 2011 Fig 1 https://www.intechopen.com/chapters/16394). Some images on copyrighted websites remain for purposes of clarity.
Keywords: 401408 Manufacturing processes and technologies (excl. textiles)